Analysis Of Illocutionary Speech Acts In The Text Of The Inaugural Speech Of A Prophet, Faculty Of Engineering, Tarumanagara University By Tri Harso Karyono - Salsabila Budi Utami; Luthfita Dina Alawiyah; Adennia Thaffana; Ariandhani Rari; Asep Purwo Yudi Utomo; Rossi Galih Kesuma; Nurnaningsih Nurnaningsih (International Journal of Educational Technology and Society, 2024)
This research aims to examine illocutionary speech acts in the text of the speech "Inauguration of Professor at the Faculty of Engineering, Tarumanagara University by Tri Harso Karyono" . A descriptive qualitative approach with content analysis method was used as the research method . Data collection is carried out by recording and marking important points which will later be used as analysis material . The research results show that in speech texts, speakers use a lot of speech that leads to illocutionary speech acts. Four types of illocutionary speech acts are found in it. Namely assertive or representative, expressive, directive and declarative illocutionary speech acts . In this research, the function or use of illocutionary speech acts and speaker strategies will be described which makes the current research different from previous research . Even though there is already a lot of research out there that examines illocutionary speech acts , the author hopes that the research carried out this time can provide benefits for the development of pragmatics and broaden readers' horizons . Not only that, it is hoped that this study will also provide benefits to the general public and students majoring in Indonesian.